ORGANIZATIONAL ORGANIZATIONAL CULTURE OF EDUCATIONAL INSTITUTION IN INDONESIA - Moh Ali (Paedagogia: Jurnal Pendidikan, 2020)
Organizational culture is defined as the underlying beliefs, assumption, values and ways of interacting that contribute to the unique social and psychological environment of an organization. There are two types of culture, i.e. material culture and non-material culture, which had been organized and maintained according to the needs of human being. Source of the culture is originated from the product of human being’s thought. Human being itself is a unique individual whose behaviour influenced by many variations and shapes of culture in society. As for the object of organizational culture in educational institution, it included quality, achievement, and professionalism which can be developed by educational institution.